An Adaptive Anti-DDoS System for IP Service Provider Backbones - Rodrigues, Alberto Savio Figueira; Santos, Fabio; Araujo, Marcos; Fernandes, Natalia Castro (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2018: Anais do XVIII Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2018.4276, 2018)
This article presents an adaptive anti-DDoS system based on SDN for IP service providers' backbones. We analyzed requirements and solutions used on current IP backbones in order to manage different anti-DDoS systems to mitigate attacks to customers or to the backbone itself. The base of our proposal is a controller that synchronizes network reaction according to the volume of attacks and the available infrastructure, using a layered protection scheme. This controller dynamically provisions virtual machines and network links based on transit virtual router and forwarding (VRF). The system is able to dynamically reconfigure itself according to attack traffic patterns. As a consequence, our system improves backbone performance and customers quality of experience by reducing the impact of DDoS traffic in a more efficient way than current solutions.